2004
DOI: 10.1159/000093686
|View full text |Cite
|
Sign up to set email alerts
|

Complex Qualitative Models in Biology: A New Approach

Abstract: We advocate the use of qualitative models in the analysis of large biological systems. We show how qualitative models are linked to theoretical differential models and practical graphical models of biological networks. A new technique for analyzing qualitative models is introduced, which is based on an effi cient representation of qualitative systems. As shown through several applications, this representation is a relevant tool for the understanding and testing of large and complex biological networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Note that, if the profile provides us with a sign for each vertex of the influence graph, the task can be accomplished simply by checking whether each non-input vertex receives at least one influence matching its variation. However, as soon as the experimental profile has missing values (which is very likely in practice), the problem becomes NP-hard (Veber et al 2004). In fact, a Boolean satisfiability problem over clauses C 1 , .…”
Section: Checking Consistencymentioning
confidence: 99%
“…Note that, if the profile provides us with a sign for each vertex of the influence graph, the task can be accomplished simply by checking whether each non-input vertex receives at least one influence matching its variation. However, as soon as the experimental profile has missing values (which is very likely in practice), the problem becomes NP-hard (Veber et al 2004). In fact, a Boolean satisfiability problem over clauses C 1 , .…”
Section: Checking Consistencymentioning
confidence: 99%
“…Qualitative Reasoning is in general computationally intensive, and the complexity can be NP-complete (Dormoy, 1988;Veber et al, 2006). The rich representation of inequality relations in Garp3, although powerful, causes the inequality reasoning inferences to be vulnerable to combinatorial explosion.…”
Section: Computational Efficiencymentioning
confidence: 99%
“…Finally, let us mention that we provided in [4] an efficient representation of qualitative systems, leading to effective algorithms, some of them could be used to get further insights into the model under study. We shall see in the next section, that these algorithms are able to deal with large scale networks.…”
Section: Analyzing a Network: A Simple Examplementioning
confidence: 99%
“…Following this line of research, we showed in previous papers (see [2,3,4]) how to define and to check consistency between experimental measurements and a graphical regulatory model formalized as an interaction graph. The purpose of the present work is to validate this methodology on a realsize setting.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation